Dissemination of Cultural Heritage : Design and Implementation of a VR environment for the preservation of art and culture in the Canton Pujilí - Ecuador. - Herrera Calvopiña, Jhoanna Gabriela (2021)
Technology through time has been a fundamental mean in the development and cultural evolution, changing the perspective of the human being with the world in relation to the reconstruction of memory and the historical past. In this context, Ecuador seeks to adapt to the rapid changes of the technological era and solve the problems caused by the pandemic caused by the outbreak of COVID-19 in early 2020, in the interruption of cultural and economic activities. At the local level, Pujilí, Land of the DANZANTE, considered intangible cultural heritage of humanity, has not been exempt from this situation, being the Cultural area the most affected. For this reason, the current research, PUJILÍ MUSEUM, proposes a means of dissemination and preservation of Art and Culture, adapted to current changes, through a Virtual Reality mobile application that integrates 3D modeling technologies and reconstruction by Photogrammetry, to improve the quality and immersion, allowing visitors to immerse themselves in a world full of history, art and culture, music, and tradition. The application was tested by 30 users/visitors who had mid/high range mobile devices, applying the convenience sampling technique, in order to know the levels of satisfaction and learning of the different interactive areas. The experimental results showed a positive effect on visitors and a high level of acceptance when using the virtual environment. This has been corroborated by the number of downloads, ratings, and reviews.